The ultimate marketing plan : target your audience! get out your message! build your brand! - Kennedy, Dan S., 1954- (Avon, Mass. : Adams Business, 2011)
As the market place changes under the impact of the rapid transformation of information and the Internet, marketing plans are more important than ever. This title explains how to integrate social media, contacts and membership, and other tools into a complete plan that strengthens your customer base without breaking your budget.
Ultimate marketing plan success factor #1: Right message -- Ultimate marketing plan success factor #2: Presentation -- Ultimate marketing plan success factor #3: Targets -- Ultimate marketing plan success factor #4: Proof -- Ultimate marketing plan success factor #5: Perception -- Ultimate marketing plan success factor #6: Heat -- Ultimate marketing plan success factor #7: Action -- Ultimate marketing plan success factor #8: Equity -- Ultimate marketing plan success factor #9: Customer multiplication -- Ultimate marketing plan success factor #10: Creating short-term sales surges -- Ultimate marketing plan success factor #11: Profitably using marketing technologies and online/internet marketing media -- Bonus Chapters -- #1: Making an ordinary business unique -- #2: The power of premiumization -- Appendix A: Ultimate marketing sins -- Appendix B: Ultimate marketing secret weapons.
P.B
Includes bibliographical references and index.
Keywords: Direct marketing -- United States; Marketing -- United States; Sales promotion -- United States; Marketing direct -- États-Unis.; Marketing -- États-Unis.; Ventes -- Promotion -- États-Unis.; Direct marketing; Marketing; Sales promotion; United States